Incorporating the Critical Music Framework: An Autoethnographic Reflection - Ender, Tommy (International Journal of Multicultural Education, 2021)
I articulate an autoethnographic narrative of using different songs to counter dominant interpretations of gender, class, immigration, slavery, and education in the social studies classroom. Framing it as the Critical Music Framework, the practice of using music addressing social issues and historical representations of women and people of color provided secondary students with reflective, learning opportunities. The resulting conversations illustrate the importance of music not just on the personal, but also the academic aspects of individuals.